KETENTUAN UMUM PERPAJAKAN DAN TATA CARA PERPAJAKAN - Dini Vientiany; Lathifah Ananda Putri; Ruli Pebrina Br Sitepu (Kampus Akademik Publiser, 2024)
This research aims to encourage the public to follow Indonesian tax regulations. Because taxes have a big role in country development, and this term is no longer foreign to us. As a result, there are many laws and regulations that define taxes in Indonesia. Tax regulations always change from period to period, even in Indonesia. Thus, new terms related to taxation emerge and the public needs to know them. Apart from that, it is has import to repite that NPWP is very good for the of the country. Therefore, this paper was written to inform readers about NPWP and increase their awareness of paying taxes. Based on the my country 1945 of Indonesia, Article 23A, regulates taxes and other mandatory tax give for state need. Tax down also give the government the authority to collect taxes. Rights and obligations related to taxes must be fulfilled by all taxpayers.